Cutaneous factors related to the risk of malignant melanoma. - Beral, V; Evans, S; Shaw, H; Milton, G (1983)
In a case-control study, 287 women with malignant melanoma were compared with 574 age-matched controls. Red hair colour at age 5 years was associated with a tripling of risk [relative risk (RR) = 3.0], blonde hair with a 60% increase (RR = 1.6) and fair skin with a doubling (RR = 2.1). Women with melanoma also reported that they tended to burn (RR = 1.4) and to freckle (RR = 1.9) after exposure to sunlight. Since fair skin, red hair, and the tendency to burn or freckle after exposure to sunlight all cluster in the same individuals, the extent to which each of these factors had an independent influence on susceptibility to melanoma was investigated. Hair colour, especially red hair, proved to be the major determinant, followed by skin colour. The reporting of above average numbers of naevi on the body was as strong a predictor of melanoma as was red hair colour (RR = 3.4). A history of psoriasis was also more common in cases than controls (RR = 3.0) as was a history of vitiligo (RR = 1.8). A history of acne appeared to be protective (RR = 0.4) as did a history suggestive of chloasma (RR = 0.6) and premature greying of the hair (RR = 0.6). These relationships were irrespective of hair and skin colour.